Update on Classic and Novel Approaches in Metastatic Triple-Negative Breast Cancer Treatment: A Comprehensive Review - Greco, Salvatore; Fabbri, Nicolò; Spaggiari, Riccardo; De Giorgi, Alfredo; Fabbian, Fabio; Giovine, Antonio (Biomedicines, 2023)
Triple-negative breast cancer (TNBC) accounts for almost 15% of all diagnosed breast cancers and often presents high rates of relapses and metastases, with generally poor prognosis despite multiple lines of treatment. Immunotherapy has radically changed the approach of clinicians towards TNBC in the last two to three years, even if targeted and specific therapeutic options are still missing; this unmet need is further justified by the extreme molecular and clinical heterogeneity of this subtype of breast cancer and by the weak response to both single-agent and combined therapies. In March 2023, the National Comprehensive Cancer Network (NCCN), the main association of cancer centers in the United States, released the last clinical practice guidelines, with an update on classic and novel approaches in the field of breast cancer. The purpose of this comprehensive review is to summarize the latest findings in the setting of metastatic TNBC treatment, focusing on each category of drugs approved by the Food and Drug Administration (FDA) and included in the NCCN guidelines. We also introduce part of the latest published studies, which have reported new and promising molecules able to specifically target some of the biomarkers involved in TNBC pathogenesis. We searched the PubMed and Scopus databases for free full texts reported in the literature of the last 5 years, using the words “triple-negative breast cancer” or “TNBC” or “basal-like”. The articles were analyzed by the authors independently and double-blindly, and a total of 114 articles were included in the review.